Middelalderens hang til det overnaturlige: Middelalderlig religiøsitet i den danske historiske roman - Csúr, Gábor Attila (Passage - Tidsskrift for litteratur og kritik, 2019)
Gábor Attila Csúr: “The Inclination to the Supernatural in the Middle Ages – A Critical Reading of Medieval Religiousness in Danish Historical Novels” The article focuses on Danish historical prose fiction from the last two centuries and analyzes how the phenomenon ‘medievalism’, i. e. the interpretation, reception and recreation of the Middle Age, has changed during this period. Stereotypes about medieval religious thought and belief and the role of the church have always been popular features of historical novels. By analyzing the depictions of religiousness, the article attempts to draw a line of development in understanding medieval culture and everyday life.